2022
DOI: 10.3389/fimmu.2022.939433
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping of Exosomes in Autoimmune Diseases: A Bibliometric Analysis (2002–2021)

Abstract: BackgroundAutoimmune diseases (AIDs) are a class of chronic disabling diseases characterized by inflammation and damage to muscles, joints, bones, and internal organs. Recent studies have shown that much progress has been made in the research of exosomes in AIDs. However, there is no bibliometric analysis in this research field. This study aims to provide a comprehensive overview of the knowledge structure and research hotspots of exosomes in AIDs through bibliometrics.MethodPublications related to exosomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 127 publications
0
60
0
1
Order By: Relevance
“…Moreover, co-cited references were analyzed by VOSviewer ( Figure 6B ) to show the most influential literature. In addition, citation burst is a valuable indicator that reflects the references of interest to researchers in a particular domain in a period ( 28 ). In our study, the top 25 references with the strongest citation bursts were identified by CiteSpace and presented in Figure 6C , among which the citation burst for duration of references.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, co-cited references were analyzed by VOSviewer ( Figure 6B ) to show the most influential literature. In addition, citation burst is a valuable indicator that reflects the references of interest to researchers in a particular domain in a period ( 28 ). In our study, the top 25 references with the strongest citation bursts were identified by CiteSpace and presented in Figure 6C , among which the citation burst for duration of references.…”
Section: Resultsmentioning
confidence: 99%
“…Bibliometrix R package (version 4.2.1) (https://www.bibliometrix.org) was used to conduct the bibliometric and visualized analysis. Besides, we used Bibliometrix to build the Bradford's Law diagram, publications geographic distribution maps, trend topic analysis, and the Sankey diagram [14][15] . Bibliometric software CiteSpace (version 6.1.R3) was used to draw the dual map of the journal [16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…It is helpful for researchers in related fields to accurately grasp the current research trends by analyzing the publication. Recently, multiple bibliometric software tools have been developed, such as VOSviewer [12][13] , CiteSpace [14][15] , and Bibliometrix R package [16][17] . Researchers can analyze, compare, and visualize results across these tools and obtain information, including authors, countries, institutions, journals, and references in the area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was shown by experimental studies that their immunomodulatory characteristic is prominently diminished upon removing EVs from MSC-secretome. Although several subtypes of nano-vesicles are currently recognized, due to the recent bibliographic studies (2002-2021), two terms, “exosomes” and “extracellular vesicles”, are yet the most frequent keywords applied to describe the role of these cell-derived membranous nano-vesicles in autoimmune diseases ( 84 , 85 ). Despite the initial trend, it is now evidenced that the impact of EV subtypes and their versatility is so critical compared to what it inferred at first ( 86 , 87 ) and should not be underestimated during designing and performing future pre-clinical experiments and clinical trials.…”
Section: Extracellular Vesicles a New Therapeutic Paradigm For Autoim...mentioning
confidence: 99%